PELUANG PENGEMBANGAN KELAPA SAWIT DI INDONESIA: PERSPEKTIF JANGKA PANJANG 2025 - R. SUSILA, WAYAN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006)
After experiencing fast growth rates in 1990th, palm oil industry in Indonesia is facing some constraints that make investors have been reluctant to invest in the industry. The aim of this paper is to analyze prospects and business opportunities of the industry, by using a long run time horizon of 2005-2025. The results of analysis indicate that the world CPO consumption is estimated to be around 41.15 – 44.45 million tones in 2025. With the world CPO production in 2004 was around 25.67 million tones, and then the opportunities to increase production by 2025 was estimated between 15.78 – 18.78 million tones. Indonesia was predicted to gain the higher share in capturing this market opportunities (40%) or around 6.31 – 7.51 million tones, equivalent to 1.80 – 2.15 million ha of area expansion. Total investment required for area expansion and CPO plants development by 2020 is estimated at Rp 57.12 – Rp 67.97 trillion. In capturing these opportunities, investors have to face 22 investment constraints, mainly limited funding sources, the negative impacts of regional autonomy, land conflict, and environmental issue.
Keywords: Palm Oil, Industry, Investor, Perspective